Kekerasan Rumah Tangga Dari Persperktif Konseling - Yuda Syahputra; Stefanus Soejanto Sandjaja; Hariyani Hariyani; Eka Nurlaili (STKIP Andi Matappa, 2020)
The purpose of study is to describe domestic violence from the perspective of guidance and counseling using a behavioral and cognitive approach. Causes of domestic violence are wrong attitudes and values about the roles of men and women, authoritative power in the family, gender inequality, lower status of women, and power over women, and heads of households that manage or control the behavior of all ordinary families called the concept of patriarchy Based on the explanation above, the need for guidance and counseling services to overcome domestic violence behavior, namely: Adler therapy, rational emotive therapy, cognitive behavioral therapy, and feminist therapy. In addition, guidance and counseling services can use three stages of family counseling according to Adler, namely: initial interviews, role playing or role playing, and interpretation or interpretation